GAMBARAN TOTAL PLATE COUNT (TPC) PADA DAGING SAPI YANG DIAMBIL DI RUMAH POTONG HEWAN (RPH) KOTA KUPANG - Jois Moriani Jacob; Erda Eni Rame Hau; Yanse Yane Rumlaklak (Partner, 2018)
The Increasing of beef consumption in Kupang City, shows that there is an increase in people's need for animal protein. However, high meat consumption can also be a threat to health if contaminated by microorganisms.This study aims to calculate the amount of microbial contamination in beef samples taken from Kupang City Slaughterhouse. 30 longissimus dorsi muscle samples were taken from RPH and taken to the Kupang City Veterinary Engineering Unit to be examined using the Total PlateCaount Test (TPC), then the bacterial colonies were calculated using a colony counter.The results of the TPC analysis show that 63.33% of the samples have TPC values that are above the normal standard, while only 36.67% are at normal values.